How to treat addicted patient with concomitant psychiatric diagnosis? - A. Y. Egorov; F. Sh. Shagiahmetov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Alcohol use disorders often co-occur with affective disorders, anxiety disorders and schizophrenia. The presence of dual diagnosis worsens the prognosis in patients. However comorbid patients rarely receive specialized treatment that addresses both conditions. This paper reviews currently available treatment options for patients with dual diagnosis, as well as addresses the issues of common neurobiological mechanisms converging on monoaminergic neurons originating from the brain stem. Particular emphasis is made on the updated role for dynorphin / kappa-opioid (KOP) receptor system modulation of the mesocorticolimbic dopaminergic circuitry - a neuronal hub playing a major role in the pathology of the majority of mental disorders and chemical addictions. The interest to the kappa-opioid system is caused by the role of endogenous opioid neuropeptide dynorphin being one of the most powerful endogenous depressants of monoaminergic (dopamine, norepinephrine, and serotonin) and glutamatergic neurotransmission in the cerebral cortex and subcortical limbic structures. This designates the strategic role for the kappa-subtype opioid receptor in regulation of mood, emotions, motivation, cognitive performance, perception and impulse control. Most of the KOP-antagonists are still being under clinical development and are not yet routinely available to clinicians. These agents are being developed for the treatment-resistant depression, bipolar, dissociative disorders and addictions. However, recently nalmefene - a new treatment for alcohol addiction, has been approved in Europe and Russia. Nalmefene is an opioid receptor antagonist with the preferential affinity to the KOP receptor. As this psychopharmacological agent carries therapeutic potential beyond substance abuse and addiction, possible clinical benefits of nalmefene in the treatment of complex comorbid patients are discussed. In comorbid schizophrenia patients the validity and necessity of the simultaneous therapy with antipsychotics and drugs used for the treatment of alcoholism (including opiate receptor blockers) were proved.